Hubungan Antara Pola Komunikasi Dalam Keluarga Dan Tingkat Stres Pada Anak Remaja : Studi Kasus Anak Remaja Wilayah Kota Bandung - Almadina Rakhmaniar (Jurnal Hukum dan Sosial Politik, 2023)
This study aims to examine the relationship between family communication patterns and adolescent stress levels in Bandung City. Using a survey method with 150 adolescent respondents aged 13-18 years, data were collected through a questionnaire measuring the dimensions of openness, support, conflict, and control in family communication as well as adolescent stress levels. Descriptive analysis showed variation in family communication patterns, with high levels of openness and support and low conflict. Pearson correlation tests showed a significant relationship between communication patterns and stress levels. Linear regression analysis revealed that openness and support in family communication significantly decreased stress levels, while conflict and control increased them. The t-test and F-test showed that the regression model was significant overall and each independent variable had a significant effect on stress levels. These findings emphasize the importance of open and supportive communication in the family to reduce stress levels in adolescents.